The Russo-Japanese War – Perceptions of War through a Forgotten Pictorial Archive - Nielsen, Jesper Sahl (Fra Krig og Fred, 2026)
The article started out as a minor research project to present selected photos from a recently discovered pictorial archive belonging to the Danish General Ellis Wolff (1856-1938). As the photos were thoroughly examined and the information that could be extracted from the archive led to several interesting stories about military attachés and civilian reporters operating in the theatre of war in Manchuria 1904-05, the project was expanded to include more than just “fun-fact photos”. Through a series of historical analyses based on the photographs in Wolff ’s archive and involving the various Western participants in the Russo-Japanese War, the war itself is examined. The war drew serious attention as it was the first time in history that two modernly equipped armies, both possessing rapid firing artillery, machine guns, wireless forms of communication etc., fought against each other in an all-out war. Although the focus in this article lies mainly on selected Danish people who in one way or another participated in the war, a variety of their international counterparts are also included. In the course of the war, many of these people would report for newspapers, others sought to gain valuable military information for possible doctrinal implementation and some people would do both. The multifaceted military intelligence gathering process and the widespread subsequent relinquishment of the obtained information in the Russo-Japanese War stand – in many ways – as a shining example of failed doctrinal implementation of efficient ways of warfare.